2006
DOI: 10.1002/bit.20859
|View full text |Cite
|
Sign up to set email alerts
|

NO removal in continuous BioDeNOx reactors: Fe(II)EDTA2− regeneration, biomass growth, and EDTA degradation

Abstract: BioDeNOx is a novel technique for NOx removal from industrial flue gases. In principle, BioDeNOx is based on NO absorption into an aqueous Fe(II)EDTA2- solution combined with biological regeneration of that scrubber liquor in a bioreactor. The technical and economical feasibility of the BioDeNOx concept is strongly determined by high rate biological regeneration of the aqueous Fe(II)EDTA2- scrubber liquor and by EDTA degradation. This investigation deals with the Fe(II)EDTA2- regeneration capacity and EDTA deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 26 publications
(32 reference statements)
1
26
0
Order By: Relevance
“…11 In this present study, the color of the solution changed from black-brown Fe(II)EDTA-NO to orange-brown Fe(III)EDTA and colorless Fe(II)EDTA finally, which was consistent with the Zhang et al 9 results (Fig. Subsequently, Fe(II)EDTA-NO was reduced continuously for 6-10 h. Based on the sudden decrease in Fe(II)EDTA concentration and the increase in pH value, Equation (5) was dominant at this stage. Figure 3 showed that the reduction rate of Fe(II)EDTA-NO by P. denitrificans in this system was more rapid during the initial 6 h. Based on the increase of Fe(II)EDTA concentration and the decrease of pH value, Equation (4) was followed in this period and glucose was used as the primary electron donor.…”
Section: Reduction Of Fe(ii)edta-no By P Denitrificans In Heterotropsupporting
confidence: 91%
See 1 more Smart Citation
“…11 In this present study, the color of the solution changed from black-brown Fe(II)EDTA-NO to orange-brown Fe(III)EDTA and colorless Fe(II)EDTA finally, which was consistent with the Zhang et al 9 results (Fig. Subsequently, Fe(II)EDTA-NO was reduced continuously for 6-10 h. Based on the sudden decrease in Fe(II)EDTA concentration and the increase in pH value, Equation (5) was dominant at this stage. Figure 3 showed that the reduction rate of Fe(II)EDTA-NO by P. denitrificans in this system was more rapid during the initial 6 h. Based on the increase of Fe(II)EDTA concentration and the decrease of pH value, Equation (4) was followed in this period and glucose was used as the primary electron donor.…”
Section: Reduction Of Fe(ii)edta-no By P Denitrificans In Heterotropsupporting
confidence: 91%
“…However, the two technologies have many disadvantages, such as high operating costs, failure-prone catalyst and NH 3 leakage. 5,6 Fe(II)EDTA is the most common absorbent because it has the ability to form stable complexes with NO. Due to the low solubility in aqueous solution, the NO removal efficiency of the biological method is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Poor NO solubility in water limits NO mass transfer in a bioreactor, resulting in the limitation of biological treatment. One promising technique for NO removal from industrial flue gasses is an integrated physico‐chemical and biological process . Aqueous solutions of ferrous chelates such as Fe II (EDTA) can be applied as scrubber liquor , .…”
Section: Introductionmentioning
confidence: 99%
“…One promising technique for NO removal from industrial flue gasses is an integrated physico‐chemical and biological process . Aqueous solutions of ferrous chelates such as Fe II (EDTA) can be applied as scrubber liquor , . In the integrated system, Fe II (EDTA) can chelate NO into the solution to form Fe II (EDTA)‐NO.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the removal of nitrogen oxides from waste gases has already become one of the most important tasks of environmental pollution treatment in the 21st century. Different catalytic removal technologies have been made by some researchers in recent years to limit the air pollutants emissions [3]- [6].…”
Section: Introductionmentioning
confidence: 99%